BRD4 Inhibition Protects Against Acute Pancreatitis Through Restoring Impaired Autophagic Flux - Shen, Shuangjun; Li, Bin; Dai, Juanjuan; Wu, Zengkai; He, Yan; Wen, Li; Wang, Xingpeng; Hu, Guoyong (Frontiers in Pharmacology, 2020)
Impaired autophagy has been shown to play a critical role in experimental and human acute pancreatitis (AP). However, the mechanism for transcriptional regulation of autophagy remains largely unknown. In this study, we aim to investigate the role of BRD4 (bromodomain-containing protein 4), a transcriptional repressor of autophagy, during AP. Changes in pancreatic BRD4 expression and the effect of BRD4 inhibition were measured in mice with AP (induced by caerulein and ethanol and palmitoleic acid) and in isolated pancreatic acinar cells stimulated with cholecystokinin (CCK). The severity of pancreatitis was assessed by serum amylase and lipase and pancreatic histology. The autophagic flux, the fusion of autophagosome and lysosome, and lysosomal degradation were evaluated. Sirtuin 1 (SIRT1) expression and the effect of SIRT1 inhibition were assessed. We found that pancreatic BRD4 expression was upregulated during various models of AP. BRD4 inhibition reduced CCK-induced pancreatic acinar cell injury and pro-inflammatory expression in vitro and protected against two models of experimental AP. Mechanistically, BRD4 inhibition restored impaired autophagic flux via promoting autophagosome-lysosome fusion and lysosomal degradation. BRD4 inhibition also upregulated SIRT1 and inhibition of SIRT1 reversed the effects of BRD4 inhibition on autophagic flux. Our data suggest that BRD4 is a potential therapeutic target for treating AP.